Strategic Institutional Strengthening Through Horizontal Integration Among Smallholder Dairy Farmer Organizations: SASPRI Region Bogor Case Study - Warcito; Uding Sastrawan; Anita Ristianingrum; Dahri; Muh Faturohman (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2026)
This study examines strategic institutional strengthening through horizontal integration among smallholder dairy farmer organizations under the coordination of the Solidarity Association of Alumni of the Indonesian People’s Animal Husbandry School (SASPRI) in the Bogor Region. A descriptive qualitative approach with a case study design was employed to analyze institutional dynamics and managerial practices. Data were collected through field observations, in-depth interviews, and document analysis, and were analyzed using qualitative descriptive techniques complemented by SWOT analysis. The results indicate that horizontal integration has been implemented at an operational and early institutional stage, as reflected in collective milk collection, coordinated production activities, and shared asset utilization. These practices contribute to improved operational efficiency and collective bargaining power. However, horizontal integration has not yet been fully institutionalized, resulting in semi-decentralized governance and continued dependence on specific actors. Internal and external strategic analysis reveals that organizational strengths are mainly derived from farmers’ experience, physical resources, and alumni network support, while key weaknesses persist in marketing management, institutional administration, and human resource incentive systems. The study concludes that horizontal integration functions as an effective institutional strengthening strategy when supported by more formalized, systematic, and long-term oriented governance arrangements. The findings contribute to agribusiness management literature by highlighting the role of alumni networks as governance agents and provide practical insights for strengthening smallholder dairy farmer organizations.